From silos to cells: Reducing repetitive jobs through sociotechnical redesign. (February 2021) - Vermeerbergen, Lander; Pless, Sam; van Hootegem, Geert; Benders, Jos
Given the negative effects of repetitiveness on employees' well-being, organisational performance and societal expenditure, it is desirable to reduce the number of repetitive jobs. So far, intervention strategies seeking to reduce the number of such jobs have mainly focused on individual jobs, without taking into consideration that these are embedded in organisational structures. Employee surveys and interviews were collected to measure changes in organisational structures and job repetitiveness in 18 different organisations, which had each participated in a sociotechnical redesign programme. The findings show that making work units responsible for a complete product or service (i.e. implementing cells), or installing semi-autonomous teams, results in a decreased number of repetitive jobs. This study underlines the impact of interventions in organisational structures on decreasing the number of repetitive jobs, and challenges current intervention strategies.